MicroRNA profiling of different exercise interventions for alleviating skeletal muscle atrophy in naturally aging rats. Issue 1 (1st December 2022) - Liang, Jiling; Zhang, Hu; Zeng, Zhengzhong; Lv, Jun; Huang, Jielun; Wu, Xiaowen; Wang, Minghui; Xu, Jiahao; Fan, Jingjing; Chen, Ning
Abstract: Background: Exercise is an affordable and practical strategy to alleviate several detrimental outcomes from the aging process, including sarcopenia. The elucidation of molecular mechanisms to alleviate sarcopenia is one of the most important steps towards understanding human aging. Although microRNAs (miRNAs) regulate muscle growth, regeneration and aging, the potential role of exercise‐mediated miRNAs during the prevention and rehabilitation of skeletal muscle atrophy upon exercise interventions remains unclear. Methods: A miRNA profile by miRNA sequencing for gastrocnemius muscle of a 24‐month‐old aged male rat model mimicking the naturally aging process was established through screening the differentially expressed miRNAs (DEMs) for alleviating aging‐induced skeletal muscle atrophy upon optimal exercise intervention. The screened miRNAs and hub genes, as well as biomarkers with the most significantly enriched pathways, were validated by quantitative real‐time polymerase chain reaction and western blotting. Results: The sarcopenia index (SI) value and cross‐sectional area (CSA) of rats from the old control (OC) group significantly decreased when compared with the youth control (YC) group ( P  < 0.001, P  < 0.01), whereas an increased SI value and an enlarged CSA of rats from the old‐aerobic exercise (OE), old‐resistance exercise (OR) and old‐mixed exercise (OM) groups were determined ( P  < 0.01, P  < 0.001, P  < 0.05; P  < 0.01, P  < 0.01, P  < 0.05). Our results demonstrate that 764 known miRNAs, 201 novel miRNAs and 505 miRNA–mRNA interaction networks were identified to be related to aging‐induced muscular atrophy. Among them, 13 miRNAs were differentially expressed ( P  < 0.05 and log2 |fold change| > 1) between the YC group and the OC group. Compared with the OC group, 7, 2 and 11 miRNAs were differentially expressed in the OE, OR and OM groups after exercise interventions, respectively. Meanwhile, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses revealed that the identified DEMs were primarily related to apoptosis, autophagy and the NF‐κB/MuRF1 signalling pathways ( P  < 0.05). Meanwhile, four DEMs (miR‐7a‐1‐3p, miR‐135a‐5p, miR‐151‐5p and miR‐196b‐5p), six hub genes ( Ar, Igf1, Hif1a, Bdnf, Fak and Nras ) and several biomarkers (LC3, Beclin1, p62, Bax, Bcl‐2 and NF‐κB/MuRF1) with the most significantly enriched pathways were confirmed, which may play a key role in muscular atrophy during the aging process. Conclusions: These findings are closely correlated with the progression of sarcopenia and could act as potential biomarkers for the diagnosis and interventional monitoring of aging‐induced skeletal muscle atrophy.